2020
DOI: 10.1155/2020/2405135
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin-1 Overexpression Attenuates Doxorubicin-Induced Cardiotoxicity by Inhibiting Oxidative Stress and Cardiomyocyte Apoptosis

Abstract: Background. Previous research has shown that peroxiredoxin 1 (Prdx1) is an important modulator of physiological and pathophysiological cardiovascular events. This study is aimed at investigating the role and underlying mechanism of Prdx1 in doxorubicin- (DOX-) induced cardiotoxicity. Cardiac-specific expression of Prdx1 was induced in mice, and the mice received a single dose of DOX (15 mg/kg) to generate cardiotoxicity. First, our study demonstrated that Prdx1 expression was upregulated in the heart and in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Thus, it can be speculated that PAL could decrease oxidative DNA damage during cerebral I/R injury. SOD catalyzes the conversion of superoxide anion radicals to hydrogen peroxide, and the latter is further reduced into molecular oxygen and water by CAT [35,36]. As a product of lipid peroxidation, MDA has been used to assess free radical levels in cerebral I/R injury [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be speculated that PAL could decrease oxidative DNA damage during cerebral I/R injury. SOD catalyzes the conversion of superoxide anion radicals to hydrogen peroxide, and the latter is further reduced into molecular oxygen and water by CAT [35,36]. As a product of lipid peroxidation, MDA has been used to assess free radical levels in cerebral I/R injury [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, whether ubiquitination pathway associated with NOXA degradation was simultaneously altered under oxidative stress conditions and how is this coordinated have been rarely reported. PRDX1, known as one member of peroxiredoxin family, has been demonstrated to have tumor-promoting 29 31 and apoptosis-inhibiting 45 47 role in several types of cancer. In this research, we found that PRDX1 staining was significantly higher in CRC tissues than in ANTs and that PRDX1 can inhibit cancer cell apoptosis by decreasing NOXA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS can induce placental dysfunction by suppression of placental angiogenesis, induction endothelial damage, and immune malfunction, which are suggested to be the underlie of PE development [ 11 ] [ 30 ],. In order to maintain cellular redox homeostasis, cells are equipped with antioxidant enzymes or nonenzymatic antioxidants, including SOD, CAT, and GSH, which can scavenge ROS and inhibit free radical formation [ 31 , 32 ]. Previous study demonstrated that the levels of SOD, CAT, and GSH were significantly lower in women with PE than in healthy women, suggesting that the antioxidant protective capacity was decreased in women with preeclampsia [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%